(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The founders of the Jadidism movement considered literature and theater to be the main means of awakening people’s consciousness. Jadids prepared textbooks and works in an understandable language for the people. The tutorials were clear and easy for those who wanted to learn to read and write. Jadids also paid special attention to the creation of literary works.